Pemberian Makanan Tambahan (PMT) in Cikondang Village for stunting preventions - Putri, Eliza Natasya; Islamiati, Fauziah Noer; Gunawan, Prima (Universitas Pendidikan Indonesia, 2024)
Stunting is a problem that causes toddlers to experience growth failure due to insufficient nutrient intake from pregnancy to the age of 24 months. Indonesia has shown a prevalence of stunting over the past decade, with recent efforts aiming to reduce it to 14% by 2024. This community service discusses various factors contributing to stunting and explores the implementation of Supplementary Feeding Programs (PMT) as a preventive measure. The study focuses on Desa Cikondang, where PMT was conducted to prevent stunting and educate the community on proper nutrition for toddlers. Through these community services, including planning, implementation, and evaluation, the study engaged with local stakeholders and observed significant results. The PMT initiative, featuring corn porridge and fruits like papaya and bananas, saw a notable increase in participation, indicating its effectiveness in preventing stunting. Despite coordination and resource allocation challenges, the community services demonstrated the importance of community involvement and targeted interventions in addressing stunting. The findings underscore the significance of early prevention efforts and community empowerment in combating stunting, with implications for similar initiatives across Indonesia.